Biocontrol of fusarium crown and root rot of fresh market tomato with trichoderma harzianum strains under greenhouse conditions - Ozbay, Nusret, author; Newman, Steven E., advisor; Hanson, Linda E., committee member; Hughes, Harrison G., committee member; Wallner, Stephen J., committee member (Colorado State University. Libraries, 2003)
Greenhouse tomato growers in the United States have few products available for chemical control of plant pathogens. Biological control of soilborne plant pathogens by antagonistic microorganisms is a potential alternative to the use of chemical pesticides during greenhouse production. Biological control experiments were conducted to test the effects of commercial and noncommercial strains of Trichoderma harzianum against Fusarium oxysporum f. sp. radicis-lycopersici on tomato plants grown in two different hydroponic media, coir and rockwool. This study also investigated effects of strains on growth of tomato seedlings under greenhouse conditions. Trichoderma harzianum is a fungus that attacks a range of economically important phytopathogenic fungi. Tomato (Lycopersicon esculentum Mill., cultivar Caruso) plants were inoculated with T. harzianum strains (PlantShield™, T22 and T95) prior to challenge with the pathogen. They were applied to growing media prior to sowing and to roots at transplanting at two inocula densities, 106 or 107 conidia/ml. The results of this study demonstrated that T. harzianum strains, especially applied at transplanting, decreased Fusarium crown and root rot incidence 79% for coir and 73% for rockwool, decreased disease severity 45% for coir and 48% for rockwool, and increased fruit yield 37% for coir and 25% for rockwool on tomato for control. The results also demonstrated that Trichoderma harzianum strains improved tomato seedling growth.
Covers not scanned.
Keywords: Tomatoes -- Diseases and pests -- Biological control; Fusarium diseases of plants -- Biological control; Root rots -- Biological control; Trichoderma